The practice and siting of royal inauguration in medieval Ireland - FitzPatrick, Elizabeth (Trinity College (Dublin, Ireland). Department of History, 1998)
This work presents the results of a detailed investigation into the ceremony and landscape setting of royal inauguration in medieval Ireland. Commencing with Giraldus Cambrensis’ controversial account of the king-making ritual of the Cenél Conaill, a series of documented rites which constituted the Irish banais rige (king’s wedding feast) are identified and discussed. Five distinct rites emerge, but their sequence of performance and the extent to which they occurred in combination is unclear. The elaborate ritual variously involved robing; the performance of a deiseal (ceremonial turn); the rite of the single shoe; proclamation; acclamation; and the surrendering of the king’s horse and raiment. The principal ritual prop and archetypal symbol of legitimate authority was the unsophisticated slat na ríghe (rod of kingship) which occurs in ceremonies as late as the sixteenth century. Additional rites may have included bathing, the chanting of the royal candidate’s genealogy, and possibly the recitation of an inaugural ode composed specially for the occasion. The ceremony culminated in feasting, and there is evidence to suggest that a creach righ (king’s raid) was the expected first duty of the newly-elected royal. There is marked continuity in the ritual props and rites, but nuances and symbolic transformations are also obvious. Some of these could be attributable to regional variations, but the majority are a reflection of ecclesiastical influence, or changes in the nature and distribution of secular power in the Gaelic polity. Places of inauguration are generally low hills lying between 50-800 feet OD, offering exceptional views from their summits. Their place-names frequently combine allusions to topography, royalty, a sept name, or a hilltop monument. Twenty-nine sites (Class A), identified as places of inauguration in reliable historical sources, were recorded in the field and subsequently classified. A further twenty-six sites (Class B), some of which display morphological affinities with the attested group, were drawn from folk tradition and the observations of travellers and antiquaries. An analysis of both categories reveals that Class A sites are characterised by a range of approximately eight different monument types, some of which are also common to the Class B sites. In both groups, enclosed and unenclosed mounds represent the more common choice of venue. Documentary and archaeological evidence is also presented for ritual furniture (in the form of stone chairs, leaca, footprint stones and rock-cut basins) which, while not always specific to inauguration, played a central role in the performance of the ceremony. Patterns of later medieval land-holding indicate that there is a tendency for some inauguration hills to be located within the freehold of the inaugurator. Chiefry residences are in many instances situated at a convenient distance to them, and there is some evidence to suggest that they had their ultimate use as lordship administrative centres.
Access restricted on volume 2 due to image copyright concerns. Please consult print copy in the Library.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin